Ilustrar, modificar, manipular: arte como questão de segurança da vida - Galindo, Dolores Cristina Gomes (2006)
The relation between art and life s sciences is old, but it began to be seen as life security problem recently. We defend that this transformation happened because of two different types of question: (1) The growing evidence of the security in the government of bodies and life and (2) the change in art from the function of mimesis (emphasising the illustrating function) to the direct intervention in bodies (body art and body modifications) and in life (biotechnological art). Moreover, we propose that the control of artistic practices is overall caused by migration to the artistic context of biosecurity and bioethics procedures that have been developed considerating scientific and wealth problematics. To understand how art became a question from the point of view of life security, we study three related movements, even if they are different, that together permit us to understand this transformation: (1) the inquisition of art from moral and from the big schools of medicine during dissections, focusing on spectacle of dead bodies; (2) the questioning of body art and body modifications from the hygienic-wealth logics, putting in evidence blood and other potentially infecting materials and (3) biotechnological art, specially in its transgenic modality questioned from biosecurity and bioethics. Biotechnological art, showing new dilemmas in technoscience in experimentation and laboratories perspective, signalises a problematic that goes over the aesthetics question, becoming a fight for the definition of what is conceived as being a space in genetic change